The Birth of the Modern Era: An Analysis of the Conquest of Byzantium - Bermana, Seftiandra; Prakoso, Lukman Yudho; Rosyida, Esa Dina Inda (PT FORMOSA CENDEKIA GLOBAL, 2024)
The conquest of Byzantium was the beginning of a new era. The conquest had a far-reaching impact on world history. This was not just a military conquest but was also the result of strategic, economic, and religious factors that had been built up over centuries. This research aims to analyze the collapse of Bayzantium, using the literature study method. The results obtained were that the collapse of Byzantium was caused by the excellent preparations made by the Ottomans.